MEMPERTAHANKAN EKSISTENSI BAHASA INDONESIA DENGAN SIKAP BERBAHASA - Isyatur Radhiyah (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
Language is a communication tool between one another. Indonesian is also not only a means of communication, but also as a unifier of the Indonesian nation. True Indonesian is a language that applies rules consistently. Indonesian language in many purposes as the official language of Indonesian has been used as an oral and written communicate, both formal and informal. Indonesian nation should be proud to have a language that can represent their feelings and thoughts. The existence of the Indonesian language in the current condition, the identity of the Indonesian language needs to be fostered and socialized by every Indonesian citizen. Mastering and loving the language of their own country as an Indonesian citizen who loves the homeland is a pride, identity, and characteristic of Indonesia because it is the language of unity. We may learn foreign languages, but that doesn't mean we should forget Indonesian and the prestige of our unified language, namely Indonesian. Loving and using Indonesian according to linguistic rules and preserving it is an involvement in maintaining the existence of the Indonesian language with a language attitude.